2013
DOI: 10.1111/aos.12020
|View full text |Cite
|
Sign up to set email alerts
|

Functional and anatomical results after a single intravitreal Ozurdex injection in retinal vein occlusion: a 6‐month follow‐up – The SOLO study

Abstract: ABSTRACT.Purpose: To evaluate the efficacy of intravitreal dexamethasone implants in eyes with cystoid macular oedema (CME) secondary to branch retinal vein occlusion (BRVO) or central retinal vein occlusion (CRVO) in the clinical everyday practice, examine the effects of early retreatment and compare the results with the GENEVA study. Methods: The charts of 102 patients (102 eyes) with CME secondary to BRVO (n = 54) or CRVO (n = 48) treated with Ozurdex at 8 centres were retrospectively reviewed. The patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 22 publications
9
74
0
3
Order By: Relevance
“…This compares favourably with results from the GENEVA trial, which showed a mean reduction of 119µm at 180 days following treatment [9], as well as other studies [14,18,19]. However there was no association between change in VA and change in CRT following treatment in our study, regardless of the baseline VA. As improvement in CRT does not necessarily reflect visual improvement, we surmise that resolution of ME on OCT scanning may leave residual macular atrophy or scarring with consequently little improvement in VA.…”
Section: Anatomical Outcomessupporting
confidence: 85%
“…This compares favourably with results from the GENEVA trial, which showed a mean reduction of 119µm at 180 days following treatment [9], as well as other studies [14,18,19]. However there was no association between change in VA and change in CRT following treatment in our study, regardless of the baseline VA. As improvement in CRT does not necessarily reflect visual improvement, we surmise that resolution of ME on OCT scanning may leave residual macular atrophy or scarring with consequently little improvement in VA.…”
Section: Anatomical Outcomessupporting
confidence: 85%
“…The relationship between duration of ME and the efficacy of DEX implant treatment seen in this study has also been reported in other studies. In the SOLO retrospective 6-month study, DEX implant treatment was associated with better improvement in CRT in BRVO of shorter duration [12]. Furthermore, in the GENEVA pivotal randomized clinical trials of DEX implant for treatment of RVO-associated ME, shorter duration of ME was associated with better improvement in BCVA and CRT after DEX implant treatment, especially in patients with BRVO [5].…”
Section: Discussionmentioning
confidence: 95%
“…Merkoudis et al 13 found a recurrence of macular edema between months 4 and 5 after the first DEX implant in eyes treated for RVO. However, other retrospective studies found a mean reinjection interval of 4.5, 5.3, and 5.6 months after treatment with DEX implants, [14][15][16] with a probable delay between recurrence and reinjection time. However, all patients with qualitative anatomical recurrence on SD-OCT imaging had functional recurrence at 14.44 days (SD = 42.18) on average after the first signs on OCT.…”
Section: Eyementioning
confidence: 87%